IMPLEMENTASI KEBIJAKAN PENINGKATAN KESEJATERAAN MASYARAKAT DI DESA TOWUNTU TIMUR KECAMATAN PASAN KABUPATEN MINAHASA TENGGARA - KANSIL, MEITA EUNIKE EKLESIA SIGAR; LENGKONG, FLORENCE DAICY; LONDA, VERY (Sam Ratulangi University, 2020)
Public welfare is the aim and effort of the government through efforts such as increasing economic growth.To improve community welfare is inseparable from the implementation of policies. In implementing existingpolicies, development must be truly carried out in accordance with what is formulated by the villageapparatus and the community. The purpose of this study was to determine the implementation of communitywelfare improvement policies in East Towuntu Village, Pasan Sub-District, Southeast Minahasa Regency.This research uses descriptive qualitative research methods. Data collection techniques used wereobservation, interviews and documentation. To see how the implementation of community welfareimprovement policies in East Towuntu Village. In terms of indicators in accordance with the research focusof researchers, namely Idealized polic, Target groups, Implementing organizations, and Environmentalfactors. In reality, the implementation of policies to improve welfare for development also has not yetbecome a priority but has been forced to work, even though the results have not yet benefited the community,and need attention to the government of East Towuntu Village. In compiling planning, the villagegovernment should conduct a comprehensive study so that the results of development are right on targetand in accordance with needs, not just thinking that the important thing is not to break the rules, in the endone of the objectives of the dandes is to improve community welfare.Keywords: Implementation, Improvement, Community welfare.